Optimization and validation of CEDIA drugs of abuse immunoassay tests in serum and urine on an Olympus AU 400. Issue 5 (6th February 2013) - Musshoff, F.; Wolters, T.; Lott, S.; Ippisch, J.; Gradl, S.; Madea, B.
Abstract : A preliminary initial cloned enzyme donor immunoassay (CEDIA) was optimized for serum and urine drug testing with respect to the German per se limits for driving under the influence of drugs (serum) and lowered cut‐offs in cases of driving licence re‐granting (urine). The tests were performed on an Olympus AU 400 auto analyzer. Validation revealed sensitivities between 93% and 100% based on comparison with data from gas or liquid chromatography coupled with mass spectrometry. Even if specificity ranged between 83% and 98 %, the tests can be considered useful for forensic purposes. Receiver operating characteristic (ROC) curves, Youden indices, as well as positive and negative predictive values are presented. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Optimization and validation of preliminary immunoassay tests with respect to the German per‐se limits for driving under the influence of drugs (serum) and lowered cut‐offs in cases of driving licence re‐granting (urine).